Compromised Anti-inflammatory Action of Neutrophil Extracellular Traps in PAD4-Deficient Mice Contributes to Aggravated Acute Inflammation After Myocardial Infarction - Eghbalzadeh, Kaveh; Georgi, Leena; Louis, Theresa; Zhao, Haizhi; Keser, Ugur; Weber, Carolyn; Mollenhauer, Martin; Conforti, Andreas; Wahlers, Thorsten; Paunel-Görgülü, Adnana (Frontiers in Immunology, 2019)
Innate immune responses and rapid recruitment of leukocytes, which regulate inflammation and subsequent healing, play a key role in acute myocardial infarction (MI). Peptidylarginine deiminase 4 (PAD4) is critically involved in chromatin decondensation during the release of Neutrophil Extracellular Traps (NETs) by activated neutrophils. Alternatively activated macrophages (M2) and accurate collagen deposition determine the repair of the infarcted heart. In this study, we investigated the impact of NETs on macrophage polarization and their role for acute cardiac inflammation and subsequent cardiac healing in a mouse model of acute MI. NETs were found to promote in vitro macrophage polarization towards a reparative phenotype. NETs suppressed pro-inflammatory macrophages (M1) under hypoxia and diminished IL-6 and TNF-α expression. Further on, NETs strongly supported M2b polarization and IL-10 expression. In cardiac fibroblasts, NETs increased TGF-ß expression under hypoxic culture conditions. PAD4-/- mice subjected to permanent ligation of the left anterior descending artery suffered from overwhelming inflammation in the acute phase of MI. Noteworthy, PAD4-/- neutrophils were unable to release NETs upon ex vivo stimulation with ionomycin or PMA, but produced significantly higher amounts of reactive oxygen species. Increased levels of circulating cell-free DNA, mitochondrial DNA and cardiac troponin were found in PAD4-/- mice in the acute phase of MI when compared to WT mice. Reduced cardiac expression of IL-6, IL-10 and M2 marker genes as well as increased TNF-α expression suggested a pro-inflammatory state. PAD4-/- mice displayed significantly increased cardiac MMP-2 expression under baseline conditions. At day 1 post-MI, PAD4-/- mice showed increased end-diastolic volume and increased thinning of the left ventricular wall. Interestingly, improved cardiac function, as demonstrated by significantly increased ejection fraction, was found at day 21. Altogether, our results indicate that NETs support macrophage polarization towards an M2 phenotype, thus displaying anti-inflammatory properties. PAD4 deficiency aggravates acute inflammation and increases tissue damage post-MI, partially due to the lack of NETs.